Bewertung von Landschaftsfunktionen mit Choice Experiments; Valuation of landscape functions using choice experiments - Kim Schmitz; P. Michael Schmitz; Tobias C. Wronka (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– The first application of choice experiments as an environmental valuation method in Germany clearly demonstrates the potential of this method for the valuation of agriculture's multifunctionality. Choice experiments are a reasonable enhancement of the conjoint analysis as they are capable of calculating the theoretically correct welfare measures in the form of implicit prices. In combination with business and ecological models this allows for the comprehensive valuation of agriculture's multifunctionality in the sense, that in addition to the supply or cost side of land use scenarios the demand or benefit side is accounted for. In this study the integrated ecological and economical valuation of land use scenarios was demonstrated for two different scenarios. The welfare changes for the regional population due to changes in the quality or quantity of several landscape functions like drinking water quality, biodiversity, food production and landscape aesthetics were calculated. The inclusion of both supply and demand in this cost-benefit study is an important step forward for the development of sustainable land use concepts.
Keywords: 330; Agrarboden; Landschaftsschutz; Conjoint-Analyse